2015
DOI: 10.4103/0970-9290.176916
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle aberration in ameloblastoma and adenomatoid odontogenic tumor: As evidenced by the expression of p53 and survivin

Abstract: There was no much difference in p53 expression in ameloblastoma and AOT suggestive of cell cycle aberration in both the odontogenic tumors, but significant difference in survivin expression in ameloblastoma and AOT with higher percentage of positive cells in ameloblastoma may be indicative of an aggressive behavior of ameloblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Other second messengers, such as Bcl-2 family (3,6), Survivin (15,25), APAF-1 (18), X chromosome-linked inhibitor of apoptosis protein (XIAP) have been reported, but there was not any functional study related to these molecules. (25) Therefore those molecules should be further investigated, so that a more complete strategy in inducing ameloblastoma into apoptosis could be obtained.…”
Section: Future Research Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Other second messengers, such as Bcl-2 family (3,6), Survivin (15,25), APAF-1 (18), X chromosome-linked inhibitor of apoptosis protein (XIAP) have been reported, but there was not any functional study related to these molecules. (25) Therefore those molecules should be further investigated, so that a more complete strategy in inducing ameloblastoma into apoptosis could be obtained.…”
Section: Future Research Perspectivementioning
confidence: 99%
“…In accordance with the expressions of apoptotic ligand and receptor in central cells, expressions of p53 (8,15), phosphatase and tensin homolog (PTEN) (16), phosphorylated-PTEN (16), phosphorylated-Jun N-terminal kinase (JNK) (17), Bcl-2 associated X protein (Bax) (3,6), Bcl-2 homologous antagonist killer (Bak) (3,5,7), caspase 9 (18), apoptotic protease activating factor-1 (APAF-1) (18), caspase 3 (19), terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) (14,20) were observed in central cells as well. Hence, some reports suggested that central cells have higher apoptotic activity than peripheral cells.…”
Section: Introductionmentioning
confidence: 99%
“…The p53 mutation leads to promotion of the function of antiapoptotic proteins. Therefore, the importance of cell cycle aberration and uncontrolled proliferation resulting from the p53 mutation is discussed [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two factors participate in the regulation of tumorigenesis by regulating cell cycle and apoptosis. [6,7] NF-κB is a key transcription factor present in the occurrence and development of tumors, and it participates in a variety of cellular biological reactions. It can enter into the nucleus after activation and regulate the expressions of encoding cytokines, growth factors, cell adhesion molecules and FAS proteins.…”
Section: Discussionmentioning
confidence: 99%